2022
DOI: 10.3389/fimmu.2022.1008795
|View full text |Cite
|
Sign up to set email alerts
|

The role of the astrocyte in subarachnoid hemorrhage and its therapeutic implications

Abstract: Subarachnoid hemorrhage (SAH) is an important public health concern with high morbidity and mortality worldwide. SAH induces cell death, blood−brain barrier (BBB) damage, brain edema and oxidative stress. As the most abundant cell type in the central nervous system, astrocytes play an essential role in brain damage and recovery following SAH. This review describes astrocyte activation and polarization after SAH. Astrocytes mediate BBB disruption, glymphatic–lymphatic system dysfunction, oxidative stress, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…Instead, the glial response has been extensively studied in experimental models of SAH. These studies showed diffuse microglial and astrocyte activation after experimental SAH ( 6 , 10 , 11 , 12 ). Following SAH, the morphology of microglia changes to an activated state, as their processes become shorter.…”
Section: Discussionmentioning
confidence: 89%
“…Instead, the glial response has been extensively studied in experimental models of SAH. These studies showed diffuse microglial and astrocyte activation after experimental SAH ( 6 , 10 , 11 , 12 ). Following SAH, the morphology of microglia changes to an activated state, as their processes become shorter.…”
Section: Discussionmentioning
confidence: 89%
“…Loss of astrocytic GJs contributes to astroglial network compromise and subsequent astrocytic apoptosis [ 144 , 145 ]. However, loss of the astrocytic GJ loss diminishes the spread of Ca 2+ waves, preventing synchronized activity between neurons and vascular SMCs [ 146 ].…”
Section: Delayed Injury (5–14 Days)mentioning
confidence: 99%
“…This cellular strategy provides another energy source (e.g., astrocyte–neuron lactate shuttle) for neurons during periods of excessive energy demand [ 150 ]. In SAH, astrocytic apoptosis is favored to precede neuronal apoptosis [ 145 ].…”
Section: Delayed Injury (5–14 Days)mentioning
confidence: 99%
“…Astrocytes are part of the cerebral glia, tasked with the regulation of synaptic transmission, NVU function, and maintenance of blood-brain barrier integrity via their endfeet ( Figure 4 ) [ 72 , 73 , 74 ]. Under physiological conditions, they inhibit CSD initiation via K+ buffering through Na-K ATPase and glutamate uptake through GLT-1 receptors [ 53 ].…”
Section: The Interplay Between Cortical Spreading Depolarization and ...mentioning
confidence: 99%
“…SAH patients exhibit high levels of circulating and CSF glial fibrillary protein, a marker of astrocyte activation [ 74 ]. Activated astrocytes potentiate neuroinflammation via the secretion of IL-1, IL-6, TNF-alpha, and Interferon-gamma.…”
Section: The Interplay Between Cortical Spreading Depolarization and ...mentioning
confidence: 99%